Metastasis patterns and prognosis in young breast cancer patients: A SEER database analysis - Zhang, Weifang; Wu, Shang; Liu, Jinzhao; Zhang, Xiangmei; Ma, Xindi; Yang, Chao; Cao, Miao; Zhang, Shuo; Liu, Yunjiang (Frontiers in Oncology, 2022)
Background: There are few studies on young patients with MBC. This study aims to explore the metastasis pattern and prognosis of young patients with MBC. Methods: 6336 MBC patients diagnosed in the Surveillance, Epidemiology and End results (SEER) database from 2010 to 2015 were selected. They were divided into three age groups: the younger group (≤40 years old), middle-aged group (41-69 years old) and older group (≥70 years old). χ2 test was used to compare clinicopathological characteristics. Survival differences were compared by Kaplan–Meier analysis. Cox regression models were used to determine the prognostic factors affecting survival. Results: Finally, 494 patients (7.8%) ≤40 years old, 3957 patients (62.5%) 41-69 years old, and 1885 patients (29.7%) ≥70 years old were included. In younger group, the proportion of liver metastasis was significantly higher than that in middle-aged group and older group; the proportion of lung metastasis was significantly lower than that of the older group, but there was no significant difference with the middle-aged group. Kaplan-meier analysis showed that the younger group had the best prognosis and the older group had the worst. Youth is an independent protective factor for survival.In the young group, liver metastasis had the best prognosis among all metastatic sites, and HR-/HER2+ had the best prognosis among all molecular subtypes. Conclusions: The disease in young MBC patients is more aggressive but has a better prognosis, especially in liver metastases and the HR-/HER2+ subtypes.